Differential Effects of an Early Childhood Care Preventive Intervention Program on Behavior and Emotional Problems - Zarra-Nezhad Maryam; Moazami-Goodarzi Ali; Muotka Joona; Hess Markus; Havu-Nuutinen Sari; Scheithauer Herbert (SPRINGER, 2025)
Early childhood is a crucial time for developing social-emotional skills, offering the opportunity to lay the foundation for healthy development. However, early childhood behavior problems are risk factors for problems and disorders in later life phases, including depression, antisocial behavior, and substance abuse. This study uses a longitudinal design to examine the differential impact of a preventive intervention and social-emotional learning program (Papilio-3to6) on children's social-emotional development. The program was evaluated using a 1-year-randomized controlled trial design with an intervention (IG) and control group (CG) that provided data at a pretest and post-test. Teachers rated 627 children's behaviors (M-AGE = 56.77 months at pretest) from 50 daycare center groups using the Strengths and Difficulties Questionnaire (SDQ). To investigate differential effectiveness, a latent profile analysis at the pretest identified three distinct subgroups of children with different patterns in SDQ subscales: 1) Internalizers with high internalizing problems, 2) Prosocials with high prosocial behaviors, and 3) Externalizers with high externalizing problems. Latent change score analysis showed significantly reduced externalizing problems and increased prosocial behaviors in the IG compared to the CG. Further, the children categorized as Internalizers, Prosocials, and Externalizers benefited from the program regarding externalizing problems. However, no effect was found regarding internalizing problems.